1998
DOI: 10.1159/000055489
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of Soluble Growth Factors on Choriocapillaris Endothelial Growth and Survival

Abstract: The effects of soluble growth factors on regulating the survival and growth of choriocapillaris endothelial (CCE) cells were investigated in vitro. CCE cells were cultured in a serum-free medium in the presence or absence of various soluble growth factors. Cell growth and cell viability were assessed by counting viable cells. Results showed that acidic fibroblast growth factor (aFGF), basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) significantly stimulated CCE growth in a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
(52 reference statements)
1
8
0
Order By: Relevance
“…The physiological significance of IGF-mediated cell death protection has been shown in many cells including auditory sensory cells [1,12,21]. In the present study, both IGFBP-4 and IGFBP-5 are capable to enhance the utricular hair cell survival (Figure 3).…”
Section: Igfbps Function As Growth Factorssupporting
confidence: 58%
See 1 more Smart Citation
“…The physiological significance of IGF-mediated cell death protection has been shown in many cells including auditory sensory cells [1,12,21]. In the present study, both IGFBP-4 and IGFBP-5 are capable to enhance the utricular hair cell survival (Figure 3).…”
Section: Igfbps Function As Growth Factorssupporting
confidence: 58%
“…IGFBP-4 has been reported to have a predominant inhibitory effect [28], and IGFBP-5 has been found to both inhibit and potentiate the action of IGF-I in other cell types [29 Á31]. Binding ability between IGFBPs and IGF-I generally occurred in the range 1 Á100 /nmol [21], which was used in the present study.…”
Section: Igfbp-4 Has An Igf-i Inhibitory Actionmentioning
confidence: 99%
“…In vitro, VEGF inhibits the apoptosis of endothelial cells cultured either as monolayers or as capillary-like structures (33,1,31). VEGF may impose its survival function through multiple mechanisms, including activation of the PI3-kinase/ AKT pathway (20,17), activation of the nitric oxide pathway (9), and induction of Bcl-2 and A1 (19).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies using bovine choroidal endothelial cells have shown pro-angiogenic effects for VEGF, FGF2, IGF-1 and PDGF 30 31. However, it is well recognised that there is a marked heterogeneity among endothelial cells from different species and sites,3234 making it difficult to extrapolate these results to human choroidal disease.…”
mentioning
confidence: 99%